# Simplify: Read the explanation box before answering since it might confuse you. 24a^-2 times b^3 divided by 12a^4 times b^-2 The divided by part is supposed be a division bar with the top...

Simplify:

Read the explanation box before answering since it might confuse you.

24a^-2 times b^3

divided by

12a^4 times b^-2

The divided by part is supposed be a division bar with the top being the numerator and the bottom being the demoninator.

*print*Print*list*Cite

### 1 Answer

You need to simplify the following expression such that:

`(24*a^(-2)*b^3)/(12a^4*(b^-2))`

You need to use negative power property such that:

`a^(-2) = 1/a^2`

`b^(-2) = 1/b^2`

`(24*b^3/a^2)/(12a^4/b^2) = (24/12)(b^3/a^2)*(b^2/a^4)`

Using exponential identities yields:

`(24*a^(-2)*b^3)/(12a^4*(b^-2)) = 2*(b^(3+2))/(a^(2+4))`

`(24*a^(-2)*b^3)/(12a^4*(b^-2)) = 2b^5/a^6 = 2a^(-6)b^5`

**Hence, simplifying the given expression yields `(24*a^(-2)*b^3)/(12a^4*(b^-2)) = 2a^(-6)b^5.` **